Cover Picture: Plasma Process. Polym. 11∕2017. Issue 11 (16th November 2017) - Ponraj, Sri B.; Sharp, Julie A.; Kanwar, Jagat R.; Sinclair, Andrew J.; Kviz, Ladge; Nicholas, Kevin R.; Dai, Xiujuan J.
Abstract : Front Cover: Argon plasma is generated in gas bubbles inside milk to decontaminate and extend shelf life. Plasma treatment effectively reduced bacteria and significantly increased shelf life to six weeks, while commercially pasteurized milk deteriorated after two weeks. These improvements were attributed to the plasma reactive species which interacted, through the interface, with bacteria present in the water phase of milk. Further details can be found in the article by Sri B. Ponraj et al. on page1600242 .